PRESERVING THE DEBUS AND MAWLID TRADITIONS IN THE BANTEN REGION - Ramzy Ramadhan; Abu Fakhri Ropip; Ahmad Alan Ardiyansyah; Maftuh Sujana (PT. Jurnal Center Indonesia Publisher, 2025)
Historical records show that in the early 19th century, Banten became a center for scholars in the archipelago and even in Southeast Asia, particularly in the field of Islamic studies. The Bantenese culture, which appears simple on the surface, actually possesses a high level of complexity. This article presents a portrait of Bantenese culture by focusing on two main topics: the Debus tradition and the Panjang Mawlid tradition. The study finds that the diverse folk art performances in Banten, which have been passed down through generations, are inseparable from religious influences, especially Islam.